Conformational Transitions of the Cross-linking Domains of Elastin during Self-assembly - Reichheld, Sean E. (American Society for Biochemistry and Molecular Biology, 2014)
Elastin is the intrinsically disordered polymeric protein imparting the exceptional properties of extension and elastic recoil to the extracellular matrix of most vertebrates. The monomeric precursor of elastin, tropoelastin, as well as polypeptides containing smaller subsets of the tropoelastin sequence, can self-assemble through a colloidal phase separation process called coacervation. Present understanding suggests that self-assembly is promoted by association of hydrophobic domains contained within the tropoelastin sequence, whereas polymerization is achieved by covalent joining of lysine side chains within distinct alanine-rich, α-helical cross-linking domains. In this study, model elastin polypeptides were used to determine the structure of cross-linking domains during the assembly process and the effect of sequence alterations in these domains on assembly and structure. CD temperature melts indicated that partial α-helical structure in cross-linking domains at lower temperatures was absent at physiological temperature. Solid-state NMR demonstrated that β-strand structure of the cross-linking domains dominated in the coacervate state, although α-helix was predominant after subsequent cross-linking of lysine side chains with genipin. Mutation of lysine residues to hydrophobic amino acids, tyrosine or alanine, leads to increased propensity for β-structure and the formation of amyloid-like fibrils, characterized by thioflavin-T binding and transmission electron microscopy. These findings indicate that cross-linking domains are structurally labile during assembly, adapting to changes in their environment and aggregated state. Furthermore, the sequence of cross-linking domains has a dramatic effect on self-assembly properties of elastin-like polypeptides, and the presence of lysine residues in these domains may serve to prevent inappropriate ordered aggregation.